Pengaruh Dana Pihak Ketiga, Non Perfoming Financing, dan Inflasi terhadap Pembiayaan Mudharabah pada Bank Umum Syariah - Dita Puspita; Benny Barnas; Radia Purbayati (Jurusan Akuntansi Politeknik Negeri Bandung, 2022)
This study aims to determine the effect of Third Party Funds (TPF) (X1), Non Performing Financing (NPF) (X2), and Inflation (X3) on Mudharabah Financing (Y) at Islamic Commercial Banks in Indonesia. This study uses secondary data for the 2016-2020 period which is sourced from the official website of the Financial Services Authority and the Indonesian Central Statistics Agency. The analysis used is multiple linear regression analysis with quantitative methods. Simultaneously Third Party Funds (DPK), Non Performing Financing (NPF) and inflation simultaneously affect mudharabah financing. Partially, Third Party Funds (TPF) have a significant negative effect on mudharabah financing, Non-Performing Financing (NPF) has a significant positive effect on mudharabah financing, and inflation has no effect on mudharabah financing.